Nutritional Status of School Children Attending Private and Public Schools in Anyigba, Kogi State - , Achadu Abraham Eleojo; , Umeh Chisom Charles; , Alabi Deborah Aderoju (Archives of Current Research International, 2019)
Under nutrition continues to be a primary cause of ill health among children in developing countries. Adequate nutrition is critical for optimal growth, health and development of children. The objective of the present study was to assess the nutritional status of school age children (6-12 years) attending public and private schools in Anyigba as well as certain pertinent socio economic and demographic factors. Subjects were randomly selected for the study. Consent was obtained from the parent(s) or guardian(s) through the head teachers and principals of the various schools to allow the selected children to participate in the study. Ethical clearance was obtained from the Health Research Ethics Committee, Kogi State Ministry of Health. With the aid of a validated semi structured questionnaire, interview was conducted to obtain information on demographic, household characteristics and hygiene practices after obtaining informed consent from the target population. Anthropometric measurements were carried out to ascertain the nutritional status of the subjects. Results on nutritional status of subjects revealed 79.0% underweight, 1.0% obesity, 6.0% overweight and 14.0% normal weight. Community and school based nutrition programs should be established to tackle the problems of malnutrition considering the severity of malnutrition as identified in this study.